Hubungan Pupuk NPK, Dolomit, dan Curah Hujan Terhadap Produksi Kelapa Sawit (Elaeis gueneensis Jacq) Di Kebun Rengat Barat Riau - Azmi Ulul Ariga; Farida Hariani; Iwan Hasrizart (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2024)
Oil palm (Elaeis guineensis Jacq) is a leading plantation crop that is the largest contributor to foreign exchange in Indonesia. This study aims to determine the effect of NPK fertilizer, dolomite and rainfall on oil palm production in West Rengat Plantation, Riau. This research was conducted from June to August 2023. The research was conducted using the survey method. First determine the research location or land to be studied, then look for data on land area, after that determine the block that will be used as sampling. After the production data, fertilization data and rainfall data were obtained, the data were then processed using simple and multiple regression methods, so that the relationship between production and fertilization and rainfall was illustrated. The results showed that the application of dolomite fertilizer was positively correlated not significantly on the parameters of the number of bunches per hectare, number of bunches per staple, weight per hectare, and weight per length, the application of NPK fertilizer was positively correlated not significantly on the parameters of the number of bunches per hectare, number of bunches per hectare, weight per hectare, and weight per length, rainfall had a significant negative correlation on the parameters of number of bunches per hectare, number of bunches per hectare, weight per hectare, weight per length, while the interaction of dolomite fertilizer, NPK, and rainfall had a significant effect on weight per length. However, the effect of dolomite fertilizer, NPK, and rainfall was not significant on the number of bunches per hectare, number of bunches per stem, and bunch weight per hectare.